SOCIAL MEDIA INFLUENCER, TRUST, AND RELIABILITY ON CONSUMER BRAND PERCEPTION - Destina, Jenny; Masnita, Yolanda; Kurniawati, Kurniawati (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2026)
Abstract Increasing demand for understanding landscape of Indonesia consumer brand perceptions motivates this study. This study aims to examine the influence of social media influencers, trust, and reliability in regards to consumer brand perception in Indonesia. As well as providing another perspective toward several contradicting research such as implication that some variables might not affect consumer brand perception. By understanding the correlation in hopes of understanding further its effect on local consumers and the market. A quantitative approach was taken by collecting online survey from 219 respondents. Survey is spread through social media, correlating with respondents’ active habit on social media, with confirmed familiarity with Indonesia’s consumer brands by showcasing several general brands that exist in Indonesia market. Statistical analysis indicates that social media influencers, trust, as well as reliability having a positive effect on consumer brand perception. Implicating the correlating effect as well as several recommendations relating to the results. One of the main recommendations is maintaining and increasing consumer perception in a positive light with social media influencers. Further research on specific social media, age group, or demographics should be put to consideration as narrowing the study will help in understanding several dominant or even niche markets locally. Keywords: influencer, trust, reliability, consumer brand perception